Integrated Problem Based Learning Differentiated Instruction: An Effort to Improve Students' Literacy Numeracy Skills - Rosita, Cita Dwi; Setiyani, S; Cartini, Nining (Universitas Sarjanawiyata Tamansiswa, 2025)
The critical problem in this research is the lack of instructional strategies that simultaneously enhance literacy and numeracy skills while addressing students' diverse learning needs. While the Problem Based Learning model fosters problem-solving, its implementation often overlooks individual differences, making its integration with differentiated instruction crucial and challenging. One of the mathematical skills that students must have is literacy numeracy skills. However, based on initial observations at one of the public senior high schools in Kuningan, students' literacy and numeracy abilities are still low. This study aims to examine the effectiveness of the Integrated Problem Based Learning Differentiated Instruction model in improving high school students’ literacy and numeracy skills. The research employed an experimental method with a one-group pre-test and post-test design involving 36 class XI students. Data were collected through literacy numeracy tests administered before and after the intervention. Data analysis was conducted using N-gain to measure the improvement in students' literacy numeracy ability. The research results were obtained from test results N-Gain, with scores of 0.56 (medium category) and an increase percentage of 56.05%. Students show better abilities in understanding, interpreting, and analyzing problem-based questions related to mathematical concepts